Report of the Committee on the Status of Minority Groups in the Economics Profession - Darity, William A; Becker, Charles; Conrad, Celia A (American Economic Review, 2001)
Report of the Committee on the Status of Minority Groups in the Economics Profession by William Darity Jr. and Cecilia A. Conrad. Published in volume 91, issue 2, pages 497-501 of American Economic Review, May 2001